A Home Balance Exercise Program Improves Walking in People With Cerebellar Ataxia. (October 2014) - Keller, Jennifer L.; Bastian, Amy J.
Background. Physical therapy intervention is the primary treatment for gait ataxia and imbalance in individuals with cerebellar damage. Our aim was to determine if a home balance exercise program is feasible for improving locomotor and balance abilities in these individuals. Methods. A total of 14 patients with cerebellar ataxia participated in a 6-week individualized home-based balance exercise program and attended 5 testing sessions (2 pretraining, 1 midtraining, 1 posttraining, and 1 one-month follow-up visit). Pretraining, posttraining, and follow-up testing included a neurological assessment, clinical gait and balance tests, and laboratory assessments of balance and walking. Participants kept logs of the frequency and level of balance challenge during their training. Results. Walking speed improved across visits, as did stride length, percentage double-limb support time, Timed Up and Go (TUG), and Dynamic Gait Index. Post hoc comparisons in these measures revealed that significant rehabilitative improvements occurred over the 6-week training period, and all but TUG gains were retained 1 month later. There were no changes across the other measures for the group. Regression analysis indicated that improvements in walking speed were affected by the level of balance challenge but not by age, ataxia severity, proprioception, or duration of exercise. Conclusions. Improvement in locomotor performance in people with cerebellar ataxia was observable after a 6-week home balance exercise program. The exercise program must be designed to provide a significant challenge to the person's balance.